1998
DOI: 10.1007/s002669900227
|View full text |Cite
|
Sign up to set email alerts
|

Motivation for Rhinoplasty: Changes in 5970 Cases, in Three Groups,1964 to 1997

Abstract: The motivational factors were divided into three categories: (1) independent decision, (2) observation of previous patients, and (3) external influences. The results of the percentage breakdown of the patients in our present study are compared with previous results are presented in 1983 in this journal. Once again, the independent decision of the patient was the most important factor in deciding to have cosmetic rhinoplasty, followed by their observation of results in other patients. These two factors have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 8 publications
1
8
0
2
Order By: Relevance
“…12 In another study done on 5970 cases with motivation to cosmetic surgery, determined that most people with upper age for doing cosmetic surgery need for a foreign confirmed by their friends although these people have motivation for cosmetic surgery or Rhinoplasty from youthful. 22 A review of studies showed that the impact of patients, in particular young women from relatives and friends play an important role in pushing them toward cosmetic surgery that our study showed this influence. Another effective factor on Rhinoplasty was the impact of the media and advertising, TV commercials, magazines and journals, social networks such as Facebook and Twitter and satellites with the introduction of modern methods of cosmetic surgery affect their contacts.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…12 In another study done on 5970 cases with motivation to cosmetic surgery, determined that most people with upper age for doing cosmetic surgery need for a foreign confirmed by their friends although these people have motivation for cosmetic surgery or Rhinoplasty from youthful. 22 A review of studies showed that the impact of patients, in particular young women from relatives and friends play an important role in pushing them toward cosmetic surgery that our study showed this influence. Another effective factor on Rhinoplasty was the impact of the media and advertising, TV commercials, magazines and journals, social networks such as Facebook and Twitter and satellites with the introduction of modern methods of cosmetic surgery affect their contacts.…”
Section: Discussionsupporting
confidence: 56%
“…In our study, most of women were in age group 15-22 and the mean age of women in our study was lower than Veale and Babuccu studies. 8,17,20,22,27 So one of the things that should be noted about cosmetic surgery, is that patients who are young in age and some of them were in growing age. Here the role of plastic surgeons is important that a correct judgment about whether a young woman is a good candidate for doing cosmetic surgery or not.…”
Section: Discussionmentioning
confidence: 99%
“…This increases the potential for dissatisfaction with outcome, no matter the technical success of the operation, and should be elucidated from the patient history. 26 The surgeon should also consider that drastic cosmetic alterations can alter long-held self-image beliefs that matured over decades. Significant alterations to the nose may also affect patient family bonds via alteration of similar familial traits related to a dominant feature (i.e., large dorsal hump).…”
Section: Psychology Of the Aging Patientmentioning
confidence: 99%
“…Im Rahmen einer Untersuchung zur Motivation von 1930 Patienten zur ästhetischen Rhinoplastik in einem Zeitraum von 6 Jahren stellten Shulman et al fest, dass sich Män-ner zunehmend einer ästhetischen NasenOp. unterzogen [20]. Der Anteil ausländi-scher Patienten in der Stichprobe liegt mit 25,7% gegenüber 12,1% bzw.…”
Section: Patientenherkunftunclassified